2012
DOI: 10.1155/2012/190654
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Behavior and Physical Activity Are Independent Predictors of Successful Aging in Middle-Aged and Older Adults

Abstract: Background. Sedentary behavior is emerging as an important risk factor for poor health. Physical activity has proven to be important in determining overall successful aging (SA) among older adults; however, no data exists on the influence of sedentary behavior on SA. The purpose of this analysis was to determine whether there is an association between sedentary behavior and successful aging, independent of physical activity levels. Methods. 9,478 older (M = 4,245; F = 5,233) and 10,060 middle-aged (M = 4.621; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
149
1
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(174 citation statements)
references
References 31 publications
5
149
1
12
Order By: Relevance
“…Less sedentary behavior has been found to be an independent predictor of successful aging among individuals ≥45 years of age. 781 Moreover, prolonged bouts of sedentary behavior and total amount of physical inactivity appear to be independently related to risk factors associated with metabolic syndrome (eg, increased waist circumference, body mass index, triglycerides, and plasma glucose). 782 To date, little research has been conducted on patterns of sedentary behavior after stroke.…”
Section: Motor Impairment and Recovery: Deconditioning And Fitness Afmentioning
confidence: 99%
See 1 more Smart Citation
“…Less sedentary behavior has been found to be an independent predictor of successful aging among individuals ≥45 years of age. 781 Moreover, prolonged bouts of sedentary behavior and total amount of physical inactivity appear to be independently related to risk factors associated with metabolic syndrome (eg, increased waist circumference, body mass index, triglycerides, and plasma glucose). 782 To date, little research has been conducted on patterns of sedentary behavior after stroke.…”
Section: Motor Impairment and Recovery: Deconditioning And Fitness Afmentioning
confidence: 99%
“…A cohort study reported that people after stroke (n=25) spent less time being physically active and had fewer breaks in sedentary behavior at 1 week, 3 months, and 6 months after stroke compared with nondisabled control subjects matched by age, sex, and body mass index. 781 Intervention strategies are needed to break the relentless poststroke cycle of reduced physical activity leading to further reductions in functional capacity and heightened risk of secondary complications. The central role that aerobic exercise plays in improving cardiorespiratory fitness is well known and strongly supported by evidence.…”
Section: Motor Impairment and Recovery: Deconditioning And Fitness Afmentioning
confidence: 99%
“…25 For this study, data collected during sleep were excluded. Using the energy expenditure (EE) data from the SWA, we categorized PA intensity into three levels: mild, moderate, and vigorous PA. 26 Mild PA consisted of activities yielding an EE of 1.6-2.9 metabolic equivalents (METs); moderate PA, an EE of 3.0-4.9 METs; and vigorous activity, an EE of 5.0 METs or more. 27,28 Procedures…”
Section: Physical Activitymentioning
confidence: 99%
“…[2] The World Health Organization calls for a 10% increase in physical activity (PA), and encourages community-based collaborations to formulate evidence based, cost-effective means to achieve this goal. [3] PA can decrease the chance of falls, [4] cardiovascular disease, [5] and arthritis pain. [6][7][8] PA can increase memory performance [9] and improve functioning with arthritis.…”
Section: Introductionmentioning
confidence: 99%